Raspberry, not a car: context predictability and a phonological advantage in early and late learners’ processing of speech in noise - Gor, Kira (Frontiers in Psychology, 2014)
Second language learners perform worse than native speakers under adverse listening conditions, such as speech in noise. No data are available on heritage language speakers’ (early naturalistic interrupted learners’) ability to perceive speech in noise. The current study fills this gap and investigates the perception of Russian speech in multi-talker babble noise by the matched groups of high- and low-proficiency heritage speakers and late second language learners of Russian who were native speakers of English. The study includes a control group of Russian native speakers. It manipulates the noise level (high and low), and context cloze probability (high and low). The results of the speech in noise task are compared to the tasks testing the control of phonology, AXB discrimination and picture-word discrimination, and lexical knowledge, a word translation task, in the same participants. The increased phonological sensitivity of heritage speakers interacted with their ability to rely on top-down processing in sentence integration, use contextual cues, and build expectancies in the high-noise/high-context condition in a bootstrapping fashion. Heritage speakers outperformed oral proficiency-matched late second language learners on speech in noise task and two tests of phonological sensitivity. The outcomes of the speech in noise experiment support both the early naturalistic advantage and the role of proficiency in heritage speakers. Heritage speakers’ ability to take advantage of the high-predictability context in the high-noise condition was mitigated by their level of proficiency. Only high-proficiency heritage speakers, but not any other nonnative group, took advantage of the high-predictability context that became available with better phonological processing skills in high noise. The study thus confirms high-proficiency (but not low-proficiency) heritage speakers’ nativelike ability to combine bottom-up and top-down cues in processing speech in noise.